Multidimensional poverty measurement and analysis : chapter 3 - overview of methods for multidimensional poverty assessment - Alkire, S; Foster, J; Seth, S; Santos, M; Roche, J; Fernandez, P (2015)
This chapter presents a constructive survey of the major existing methods for measuring multidimensional poverty. Many measures were motivated by the basic needs approach, the capability approach, and the social inclusion approach among others. This chapter reviews Dashboards, the composite indices approach, Venn diagrams, the dominance approach, statistical approaches, fuzzy sets, and the axiomatic approach. The first two methods (dashboard and composite indices) are implemented using aggregate data from different sources ignoring the joint distribution of deprivations The other methods reflect the joint distribution and are implemented using data in which information on each dimension is available for each unit of analysis. After outlining each method, we provide a critical evaluation by discussing its advantages and disadvantages.